2023
DOI: 10.3390/bioengineering10030315
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Coupled MBS and FEM Models of the Spine—A Review

Abstract: How back pain is related to intervertebral disc degeneration, spinal loading or sports-related overuse remains an unanswered question of biomechanics. Coupled MBS and FEM simulations can provide a holistic view of the spine by considering both the overall kinematics and kinetics of the spine and the inner stress distribution of flexible components. We reviewed studies that included MBS and FEM co-simulations of the spine. Thereby, we classified the studies into unidirectional and bidirectional co-simulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…Although respective muscle-related parameters can be derived in vivo from imaging data ( Niklasson et al, 2022 ), the mechanical properties of passive structures can currently only be determined with the help of in vitro studies ( Panjabi et al, 1976 ; Pintar et al, 1992 ; Ashton-Miller and Schultz, 1997 ; Heuer et al, 2007 ; White, 2022 ), which require the isolation of the structure of interest to mount them in respective testing machines and therefore cannot represent the mechanical properties of the modeled subject. In order to obtain consistent datasets for biomechanical models, alternative, noninvasive methods must be developed to determine these parameters in large subject cohorts, e.g., using a combination of experimental studies, multimodal imaging, and artificial neural networks (ANNs), as suggested in earlier publications ( Lerchl et al, 2023 ; Nispel et al, 2023 ). Furthermore, we neglected the effects of intraabdominal pressure (IAP) on spinal biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Although respective muscle-related parameters can be derived in vivo from imaging data ( Niklasson et al, 2022 ), the mechanical properties of passive structures can currently only be determined with the help of in vitro studies ( Panjabi et al, 1976 ; Pintar et al, 1992 ; Ashton-Miller and Schultz, 1997 ; Heuer et al, 2007 ; White, 2022 ), which require the isolation of the structure of interest to mount them in respective testing machines and therefore cannot represent the mechanical properties of the modeled subject. In order to obtain consistent datasets for biomechanical models, alternative, noninvasive methods must be developed to determine these parameters in large subject cohorts, e.g., using a combination of experimental studies, multimodal imaging, and artificial neural networks (ANNs), as suggested in earlier publications ( Lerchl et al, 2023 ; Nispel et al, 2023 ). Furthermore, we neglected the effects of intraabdominal pressure (IAP) on spinal biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…П и т а н н я щ о д о р о з р а х у н к у ф а к т и ч н о г о навантаження на МХ Д поперекового від ділу в статичному положенні та в динаміці, з урахуванням усіх чинників, що його визначають і впливають на нього, не вирішено. Спроби його розв'язання здійснюють постійно [50,53,68,78,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] 7]. У зв'язку із цим, максимальне вилучення поперекового згинання із фізичної активності вранці може зменшити маніфестацію болю в попереку [109,110].…”
Section: вузькі стежки біомеханіки хребтаunclassified
“…Similarly, Wong et al [ 13 ] used FEMs to evaluate the stress of different thoracolumbar reconstruction constructs on proximal junctional levels, providing insights on the optimal selection of reconstruction constructs to treat thoracolumbar burst fractures and minimize postoperative complications. In addition, Nispel et al [ 14 ] reviewed the contemporary use of coupled multibody models and FEM simulations to analyze both the holistic biomechanics of the spine and the stress distribution within flexible components (e.g., intervertebral discs), providing a more comprehensive view of facilitating the evaluations and diagnoses of spine-related health issues.…”
Section: Evaluation Of Motion Patterns Using Validated Biomechanical ...mentioning
confidence: 99%